Історичні проблеми та политика пам’яті в польсько-українських стосунках (1991 – 2017) - Jędraszczyk, Katarzyna, Катажина Єндращик (ІПіЕНД ім. І.Ф. Кураса НАН України, 2018)
The article is an attempt to impose on the chronology of bilateral relations between Poland and Ukraine the analysis of the themes and political contexts related to historical policy emerging in these relations. The article analyzes the activities of Polish and Ukrainian authorities in the area of historical policy, related to the interpretation of difficult historical topics from the 20th century.Ukraine and Poland according to Troebst are countries where the culture of memory has become a field of conflict between two large political camps. The policy of memory in both countries may change as new ruling groups come to power. This also means that bilateral relations are vulnerable to instability. In Polish-Ukrainian relations after 1991 such a small dimension, first of all, related to the history of the Borderlands: fighting in Lviv and the role of Lviv Eaglets (Cemetery of the Lviv Eaglets), crimes of the OUN-UPA in Volyn and the issues of commemorating the victims and interpretation of the meaning of OUN-UPA and its leaders in the history of Poland and Ukraine.
Keywords: Україна, Польща, історична політика, двосторонні відносини, ОУН-УПА, Волинь, Меморіал львівських орлят, Ukraine, Poland, historical policy, bilateral relations, OUN-UPA, Volyn, Cemetery of the Lviv Eaglets. Ukraina, Polska, relacje dwustronne, polityka historyczna, Wołyń, OUN-UPA, Cmentarz Orląt Lwowskich